Protecting Nature and Displacing People - Vandergeest, Peter (Refuge: Canada's Journal on Refugees, 1997)
We usually think that national parks,wildlife sanctuaries, and other areas reservedfor the protection of nature aregood things but the displacement effectsof protected areas have made themhighly controversial in many parts ofthe world. However, many environmentalgroups see an expanded protectedareas system as central to thepreservation of both biodiversity and the"charismatic megafauna" which are thebasis of their funding drives. Based on adiscussion of the historical roots of protectedareas, the globalization of natureprotection and local people in conservation,this article offers alternatives to thedisplacement of rural populations in thename of nature conservation.